2012
DOI: 10.1007/s00221-012-3005-z
|View full text |Cite
|
Sign up to set email alerts
|

Vision-to-event and movement-to-event coordination in an unimanual circling task

Abstract: Coordination of actions with events in extracorporeal space is essential for many everyday tasks. In the present study, we investigated how transformations, like in tool use, and varying the spatial context affect action coordination. For this aim, we used a circling task that required participants to coordinate the visual feedback of hand movements with a clockwise circling stimulus (event). The trajectories of stimulus and visual feedback were presented horizontally aligned (group horizontal), within each ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 35 publications
6
14
0
Order By: Relevance
“…Research on bimanual coordination (i.e., the coordination of the two hands) has also included tasks without discrete structuring events, like circling (e.g., Swinnen et al, 1997; Mechsner et al, 2001; Tomatsu and Ohtsuki, 2005). Unimanual coordination of continuous movements in tasks without structuring events has rarely been investigated, and little is known how tool transformations affect coordination in such tasks (but see Dietrich et al, 2012; Rieger et al, 2014). Specifically, to the best of our knowledge it has not been investigated how the magnitude of an angular shift transformation between a movement and its visual feedback in the environment affects coordination performance in circling movements.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research on bimanual coordination (i.e., the coordination of the two hands) has also included tasks without discrete structuring events, like circling (e.g., Swinnen et al, 1997; Mechsner et al, 2001; Tomatsu and Ohtsuki, 2005). Unimanual coordination of continuous movements in tasks without structuring events has rarely been investigated, and little is known how tool transformations affect coordination in such tasks (but see Dietrich et al, 2012; Rieger et al, 2014). Specifically, to the best of our knowledge it has not been investigated how the magnitude of an angular shift transformation between a movement and its visual feedback in the environment affects coordination performance in circling movements.…”
Section: Introductionmentioning
confidence: 99%
“…As there can be no motor constraints related to the second hand moving, unimanual coordination depends on the perceptual characteristics of the movement feedback of the moving hand, which can be either visual and/or proprioceptive/kinesthetic. Studies indicate that coordination is predominantly governed by visual feedback in many situations (Buekers et al, 2000; Roerdink et al, 2005; Dietrich et al, 2012), even though proprioception/kinesthesis must also be taken into account (Wilson et al, 2005a,b; Dietrich et al, 2012). It also depends on the type of task whether visual or kinesthetic/proprioceptive information is more beneficial for unimanual coordination (Alaerts et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated the influence of visual information (in the form of a stimulus, or visual feedback) on the stability or other qualities of coordination [82], [83], and on the ability to learn unusual coordination patterns involving phase shifts [25], [32], [34], [84], [85], specific frequency ratios [35], or both [33]. In case of violin bowing, the primary source of feedback is the sound of the instrument, which has a direct relationship with the performer's action in a complex and nonlinear manner [6][10].…”
Section: Discussionmentioning
confidence: 99%